Performance and feeding behavior of Mediterranean river buffaloes fed different proportions of maize and sugar cane silage rations - Fundora, Orlando; Franzolin, R.; Casta?eda, Paola C.; Bautista, Irma S.; Pe?a, Yuli A. (Cuban Journal of Agricultural Science, 2013)
Four Mediterranean river buffaloes with an average live weight of 824 kg were used. Animals were individually housed in corrals with front feeding trough and automatic drinking dishes for characterizing the consumption and feeding behavior of river buffaloes fed isoenergetic and isoproteic rations. The experimental diets were formed by maize (Zea mais) silages and sugar cane (Saccharum officinarum) in four proportions in dry basis (100/0, 67/33, 33/67 and 0/100) and 3 kg daily of a concentrate mixed with the silages. A Latin square design with four periods of 21 d each, with 14 d for adaptation and 7 of collection was used. Daily consumption in DB of the silages (4.43 to 6.27 kg), of the total ration (7.15 to 8.99 kg) and of total dry matter regarding live weight (0.85 to 1.08 %) decreased (P < 0.001) as the sugar cane silage level increased in the ration. The consumption speed (1.60 to 1.32 kg h-1), the time proportions devoted to the activities of feed ingestion (16.44 to 20.37 %), rumination (32.41 to 38.66 %), water intake (1.50 to 2.08 %) and movement (1.39 to 2.55 %) did not differ between treatments, while the rest time (37.33 to 47.80 %) was lower (P < 0.01) in animals fed sugar cane silage. It is concluded that the substitution of maize silage by sugar cane silage decreased the voluntary intake while maintaining circadian patterns of silage ingestion and rumination similar to those registered in other forages. Key words: feed ingestion, rumination, rest, movement